2019
DOI: 10.5114/biolsport.2018.78903
|View full text |Cite
|
Sign up to set email alerts
|

Can we use GPS for assessing sprinting performance in rugby sevens? A concurrent validity and between-device reliability study

Abstract: The purpose of this study was to (1) provide data on maximal sprinting speed (MSS) and maximal acceleration (Amax) in elite rugby sevens players measured with GPS devices, (2) test the concurrent validity of the signal derived from a radar device and a commercially available 16 Hz GPS device, and (2) assess the between-device reliability of MSS and Amax of the same GPS. Fifteen elite rugby sevens players (90 ± 12 kg; 181 ± 8 cm; 26 ± 5 y) participated in the maximal sprinting test. A subset of five players par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 17 publications
6
62
0
1
Order By: Relevance
“…We found that the GPS systematically underestimated v max ; the MPBs of v max ranged from –3.3 to −1.0%. These results are comparable to those of Lacome et al [ 18 ], who found an overall bias of –3.0%. Buchheit et al [ 32 ] observed a positive mean bias of v max of 0.3% for 5 Hz GPS measurements.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that the GPS systematically underestimated v max ; the MPBs of v max ranged from –3.3 to −1.0%. These results are comparable to those of Lacome et al [ 18 ], who found an overall bias of –3.0%. Buchheit et al [ 32 ] observed a positive mean bias of v max of 0.3% for 5 Hz GPS measurements.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Buchheit et al [ 32 ] found that CV values of v max measured by GPS tend to be higher than those of the LPM system, and are considerably higher than the ones measured in this study. As with a max , inter-unit CV measures of v max for GPS are similar to those found by Lacome et al [ 18 ] (CV of 0.5%), but better than those reported in studies by Coutts and Duffield [ 6 ] (CV 2.3 to 5.8% for different types of GPS devices) and by Johnston et al [ 11 ] (CV of 8.1%; 15Hz GPS).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found that the GPS systematically underestimated v max ; the MPBs of v max ranged from -3.3 to −1.0%. These results are comparable to those of Lacome et al [18], who found an overall bias of -3.0%. Buchheit et al [32] observed a positive mean bias of v max of 0.3% for 5 Hz GPS measurements.…”
Section: Validity Of Speed Assessmentsupporting
confidence: 90%
“…Additionally, a vehicle offers the opportunity to wear several devices at the time. However, to date, only three GPS accuracy studies have analyzed acceleration using an object other than a person as a device carrier [16][17][18].…”
Section: Introductionmentioning
confidence: 99%